Analysis of changes in total actuarial liabilities using projected unit credit method - Rose Irnawaty Ibrahim,; Ain Nurafifah Amran, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia is projected to become an ageing country by the year 2030 with the increase in population of older people to be over 15.3%. It is affecting the government expenditure in the sustainably of providing retirement benefits to older people. This study will analyse the changes of actuarial assumptions in total actuarial liabilities of a specific group of government employees. A data set is collected from a group of government employees in a Malaysian public university under service grade of N (Administration & Support). The total actuarial liability will be calculated using the Projected Unit Credit method and actuarial assumptions such as the retirement age, mortality rate, interest rate and salary growth rate will be considered. The study found that when the retirement age is increased, the total actuarial liabilities would decrease which is the aim of a sustainable pension system. Meanwhile, the decreasing mortality rate due to population ageing will cause the total actuarial liabilities to increase. Lastly, when interest rate is high and salary growth rate is lowered, the pension system is getting better. In conclusion, it is necessary for Malaysian government to take early action to sustain the Malaysian pension system due to the occurring population ageing.